3-D diagnosis-assisted management of anomalous mandibular molar - Neelam Mittal; Isha Narang (Wolters Kluwer Medknow Publications, 2012)
This case report describes the successful non-surgical endodontic management of carious exposed three-rooted mandibular molar with four root canals detected on the pre-operative radiograph taken with 20 degrees mesial angulation and confirmed with a 64-slice helical computed tomography scan-assisted 3-D-reconstructed images. Access cavity shape was modified to locate the extra canal with respect to the distolingual root in the left mandibular first molar. Copious irrigation was accomplished with 5.25% sodium hypochlorite and 17% EDTA. Biomechanical preparation was done using protapers. Calcium hydroxide dressing was done for 1 week. The tooth was obturated using gutta percha and AH 26 root canal sealer, and it was permanently restored with composite. Clinical examination on follow-up visits revealed no sensitivity to percussion and palpation in the left mandibular first molar. Thorough knowledge of root canal variations and use of advanced diagnostic modalities lead to successful non-surgical management of the complex cases.